The Adaptive Learning Effects in Developing Coercive Digital Leadership: Efforts to Improve Lecturer Performance in Central Java Province Through Integration of Transformational Leadership, Power and Digital Intellectuality - Ratih Pratiwi; Yudithia Dian Putra; Iswati Iswati (Quantitative Economics and Management Studies, 2022)
Developing a holistic business management model that guarantees transformation and high technology-based organizations are carried out for sustained value generation and global competitiveness may provide an organization with a competitive edge. This study's objective was to investigate the performance development model of lecturers at private Islamic institutions in Central Java, which is based on coercive digital leadership and adaptive learning. This research approach employs "Explanatory Research" or explanatory study, which stresses the link between research variables (causality) by testing the hypothesis that the description includes descriptions, but the emphasis is on the relationship between variables. In order to protect anonymity, data collection is conducted by distributing questionnaires that are sent directly to the leadership of the higher education institution via the Dean of the Faculty and returned in an envelope. There are both open and closed questions. Data Analysis The research data were examined descriptively, quantitatively, and using PLS Software. In addition to the analysis of the Partial Least Square Test, an analysis of the PLS model utilizing the analytical approaches of Convergent Validity, Discriminant Validity, Convergent Validity, and Inner Model Analysis was also performed, followed by hypothesis testing and model assessment. Adaptive learning has a substantial positive effect on coercive digital leadership performance, adaptive learning has a significant positive effect on lecturer performance, and coercive digital leadership has a significant positive effect on lecturer performance, as determined by PLS analysis.